THE IMPORTANCE OF BRICKS AND MORTAR IN DETERMINING THE STRENGTH OF MASONRY WALLS - Faizah, Restu (Institut Teknologi Nasional Yogyakarta, 2024)
Brick masonry walls are a type of construction that is in great demand, because the material is easy to obtain at a cheap price. Additionally, the process does not require any special skills. The strength of the wall is greatly influenced by the strength of the materials that make it up, namely bricks and mortar as adhesive. The role of bricks and mortar in creating wall strength needs to be investigated for their effectiveness. This research aims to obtain an overview of the effectiveness of the role of bricks or mortar in forming the compressive strength of masonry walls. To get the illustration in question, a compressive strength test of mortar, brick and masonry walls was carried out which was represented by masonry prism test objects referring to ASTM C1314-07. The test results are then compared to get an idea of the relationship between the three. From the research results it can be concluded that the compressive strength of masonry walls is determined more by the compressive strength of the bricks, but is also influenced by the compressive strength of the mortar. The higher the compressive strength of the mortar, the compressive strength of the wall will increase, but it is not significant. Therefore, the use of high strength mortar is less effective in increasing wall strength.